2021
DOI: 10.1002/mar.21477
|View full text |Cite
|
Sign up to set email alerts
|

Authenticating brand activism: Negotiating the boundaries of free speech to make a change

Abstract: Activist brands commonly engage in controversies to redefine which opinions and ideas are acceptable to express publicly. We conceptualize this practice as free speech boundary work. How can activist brands negotiate the boundaries of free speech to authenticate their activist positioning? By conducting a comparative case study of 18 activist brands, we identify three controversial strategies—creating monstrous hybrids, challenging the establishment, and demonstrating exemplarity—each of them challenging the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 62 publications
(141 reference statements)
0
34
1
1
Order By: Relevance
“…Yet, contrary to most extant inquiries, we demonstrate that, instead of conservatives manifesting different preferences, their liberal counterparts respond to Grab-and-Go checkouts more favorably, and indicate greater future patronage intent thereof (Madani et al, 2021). In addition, the findings herein hint at the possibility that it might be more beneficial to implement the AI uptake for businesses with a broader liberal (vs. conservative) consumer base (Sibai et al, 2021). Moreover, according to prior work, consumers' political ideology often shares substantial correlations with other ideologies such as power distance belief, fair market ideology, as well as social dominance orientation due to their common ground in the tendency of system justification (Li et al, 2021).…”
Section: Theoretical Contributionscontrasting
confidence: 98%
“…Yet, contrary to most extant inquiries, we demonstrate that, instead of conservatives manifesting different preferences, their liberal counterparts respond to Grab-and-Go checkouts more favorably, and indicate greater future patronage intent thereof (Madani et al, 2021). In addition, the findings herein hint at the possibility that it might be more beneficial to implement the AI uptake for businesses with a broader liberal (vs. conservative) consumer base (Sibai et al, 2021). Moreover, according to prior work, consumers' political ideology often shares substantial correlations with other ideologies such as power distance belief, fair market ideology, as well as social dominance orientation due to their common ground in the tendency of system justification (Li et al, 2021).…”
Section: Theoretical Contributionscontrasting
confidence: 98%
“…The present studies raise many questions for future research of interest to marketing academics as well as marketing managers and practitioners, including what happens to brands when they are seen as engaging in cultural exploitation-that is, when brands have low psychological investment in the products they are marketing. Recent research on brand authenticity attests many brands struggle with authenticity and that actions that are perceived as inauthentic damage brand equity (Sibai et al, 2021;Vredenberg et al, 2020).…”
Section: Implications For Marketing Practitionersmentioning
confidence: 99%
“…The present studies raise many questions for future research of interest to marketing academics as well as marketing managers and practitioners, including what happens to brands when they are seen as engaging in cultural exploitation—that is, when brands have low psychological investment in the products they are marketing. Recent research on brand authenticity attests many brands struggle with authenticity and that actions that are perceived as inauthentic damage brand equity (Sibai et al, 2021; Vredenberg et al, 2020). Recognizing that how consumers make authenticity judgements is complex, Nunes et al (2021) have identified different components of authenticity, including “integrity, or the extent to which a provider is being seen as intrinsically motivated, not acting out of financial interest, and acting in accord with their sincere choices that care for their community of origin” (p. 5).…”
Section: Implications For Marketing Practitionersmentioning
confidence: 99%
“…There are three basic characteristics of this social phenomenon: (1) It has a consciousness of kind by which the members connect to each other to collectively distinguish themselves from another community, as noted in Sibai et al. ’s (2021) work on brand activism; (2) By elucidating the social dynamics of a community of self-quantifiers— consumers who track themselves with technology such as wearable devices—Charitsis et al .…”
Section: Theoretical Backgroundmentioning
confidence: 99%